Evaluation of food safety knowledge, attitude, and self-reported practices of trained and newly recruited untrained workers of two baking industries in Dhaka, Bangladesh. Issue 9 (September 2020) - Jubayer, Md. Fahad; Kayshar, Md. Shahidullah; Hossain, Md. Sajjad; Uddin, Md. Nasir; Al-Emran, Md.; Akter, Syeda Sabrina
Abstract: In Bangladesh, with the mounting esteem of bakery products, food safety issues in bakery industries are a paramount concern nowadays. In this regard, this current study was performed to evaluate food safety knowledge, attitude, and self-reported practices of two groups (160 trained and 55 new untrained) of workers from two popular baking industries in Dhaka, Bangladesh. A self-administrated questionnaire was used to acquire the data during the study. On food safety knowledge, attitude, and self-reported practices, trained workers' scores (33.01 ± 0.09, 14.86 ± 0.03, 10.66 ± 0.25, respectively) were significantly higher than the scores (9.82 ± 0.23, 10.44 ± 0.26, 5.91 ± 0.33, respectively) of newly appointed untrained workers. The quality assurance department displayed better knowledge, attitude, and self-reported practices scores than the rest of the departments of the industries. However, compared to knowledge and attitude, the self-reported practice was not up to a satisfactory level. According to the study, training can be proved effective for improving knowledge and attitude but does not always translate those into self-reported practice and behaviors. The results also reinforce the importance of conducting training for untrained workers and suggest further behavior-based food safety training for all employees. Abstract : Food science; Food safety; Baking; Food handlers; HACCP; KAP; Food industry